THE INFLUENCE OF SOCIAL MEDIA MARKETING INSTAGRAM AND BRAND IMAGE ON NIVEA MEN FACE WASH PURCHASE DECISIONS AMONG GENERATION Z IN BANDUNG - Muhamad Eri Agustian Eri; Fitri Lestari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of Instagram Social Media Marketing and Brand Image on the Purchase Decision of Nivea Men Face Wash among Generation Z in Bandung City. The study is motivated by the increasing competition in the men’s skincare industry and the strategic role of Instagram as a primary marketing platform for Generation Z consumers. A quantitative approach with descriptive and verificative methods was employed. Data were collected through questionnaires distributed to 100 male Generation Z respondents in Bandung City using a non-probability sampling technique. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The descriptive findings indicate that Social Media Marketing is perceived as relatively weak, while Brand Image and Purchase Decision are categorized as good. The verificative results reveal that both Social Media Marketing and Brand Image have a positive and significant effect on Purchase Decision, with Brand Image demonstrating a more dominant influence. These findings suggest that strengthening brand image and enhancing interactive engagement on Instagram are essential strategies to increase purchase decisions among Generation Z consumers.